Bone density in female elite gymnasts: impact of muscle strength and sex hormones - Helge, E. W.; Kanstrup, I. L. (Medicine & Science in Sports & Exercise, 2002)
PURPOSE: The aim of this study was to investigate BMD in Danish female elite gymnasts and the relationships to maximal muscle strength, sex hormone concentrations, and menstrual status. METHODS: Six artistic gymnasts, five rhythmic gymnasts, and six controls aged 15-20 yr served as subjects. BMD (g.cm-2) of lumbar spine, proximal femur, distal radius, and whole body were measured by dual-energy x-ray absorptiometry (DXA) scanning. Maximal muscle strength (Nm) was measured in isokinetic trunk extension, trunk flexion, and knee extension. Serum concentrations of estrogen and progesterone in follicular and luteal phases were evaluated. RESULTS: Three out of six artistic gymnasts had amenorrhea, and two artistic and one rhythmic gymnast experienced oligomenorrhea. BMD in artistic gymnasts was greater than controls (24-45%, P < 0.05) in all sites except whole body. BMD in rhythmic gymnasts was greater than controls (4-26%, P < 0.05) in all sites except distal radius. In gymnasts, BMD correlated to both maximal muscle strength (0.60 < r < 0.85, P < 0.05) and serum progesterone (0.65 < r < 0.75, P < 0.05). CONCLUSION: In spite of oligomenorrhea or amenorrhea, it is possible for female gymnasts to maintain a high BMD in both the axial (L2-L4) and appendicular skeleton. The correlations between BMD and maximal muscle strength and progesterone concentration in gymnasts may indicate that within the same athletic group, progesterone concentration has a permissive role in bone formation, thus affecting the positive impact of muscle strength.